Mobilidade urbana e direitos humanos – a mobilidade como meio para alcance e efetivação de direitos humanos - Severo, Thelmo Henrique de Sousa (Universidade Federal Rural do Semi-Árido, 2019)
The social right to transport was recently added to the Federal Constitution after intense popular mobilization in defense of the right to mobility. Even though it is an important aspect of any human society, mobility has always been placed by Brazilian governments in the background. This paper analyzes the relationship between urban mobility and human rights, and how the process degradation of the conditions of urban mobility led to current situations in which the lack or difficulty of transportation deprives or hinders the citizen of his human rights. Methodological strategies were used: bibliographic research, analysis of the legislation that regulates urban mobility and the examination of statistical reports on the conditions of urban mobility in several metropolitan centers and Brazilian regions. By observing the data presented in these reports and their relationship with the model of individualized motor transportation, we conclude that the lack of planning and projects aimed at urban mobility and the use of public transport negatively affect the quality of life of the citizen and his possibility to exercise rights such as work, education, leisure and culture.
Artigo Acadêmico
Keywords: Transporte; Mobilidade urbana; Direitos humanos; Transport; Urban mobility; Human rights; CIENCIAS SOCIAIS APLICADAS::DIREITO